A systematic review and meta-analysis of the epidemiological characteristics of COVID-19 in children - Fardis Vosoughi; Rangarirai Makuku; Marcarious M. Tantuoyir; Farbod Yousefi; Parnian Shobeiri; Amirali Karimi; Sanam Alilou; Ronald LaPorte; Curtis Tilves; Mohammad Hossein Nabian; Mir Saeed Yekaninejad (BMC, 2022)
Abstract Background Several individual studies from specific countries have reported rising numbers of pediatric COVID-19 cases with inconsistent reports on the clinical symptoms including respiratory and gastrointestinal symptoms as well as diverse reports on the mean age and household exposure in children. The epidemiological characteristics of COVID-19 in children are not fully understood, hence, comprehensive meta-analyses are needed to provide a better understanding of these characteristics. Methods This review was conducted in Medline, Scopus, Cochrane library, Embase, Web of Science, and published reports on COVID-19 in children. Data were extracted by two independent researchers and a third researcher resolved disputes. STATA software and the random-effect model were used in the synthesis of our data. For each model, the heterogeneity between studies was estimated using the Q Cochrane test. Heterogeneity and publication bias were calculated using the I2 statistic and Egger's/Begg's tests. Results The qualitative systematic review was performed on 32 articles. Furthermore, the meta-analysis estimated an overall rate of involvement at 12% (95% CI: 9-15%) among children, with an I2 of 98.36%. The proportion of household exposure was calculated to be 50.99% (95% CI: 20.80%-80.80%) and the proportion of admitted cases was calculated to be 45% (95% CI: 24%-67%). Additionally, the prevalence of cough, fatigue, fever and dyspnea was calculated to be 25% (95% CI: 0.16-0.36), 9% (95% CI: 0.03-0.18), 33% (95% CI: 0.21-0.47) and 9% (95% CI: 0.04-0.15), respectively. It is estimated that 4% (95% CI: 1-8%) of cases required intensive care unit admission. Conclusions The pediatric clinical picture of COVID-19 is not simply a classic respiratory infection, but unusual presentations have been reported. Given the high incidence of household transmission and atypical clinical presentation in children, we strongly recommend their inclusion in research and population-based preventive measures like vaccination as well as clinical trials to ensure efficacy, safety, and tolerability in this age group.